2006
DOI: 10.4049/jimmunol.176.4.2292
|View full text |Cite
|
Sign up to set email alerts
|

Antigen Exposure during Enhanced CTLA-4 Expression Promotes Allograft Tolerance In Vivo

Abstract: The role of CTLA-4 in tolerance is primarily inferred from knockout and blocking studies. Anti-CD45RB mediates allograft tolerance in mice by inducing CTLA-4 expression on CD4 cells, providing a novel opportunity to determine how therapeutic enhancement of CTLA-4 promotes tolerance. We now show that induced CTLA-4 expression normally resolves by day 17. Although thymectomy prolongs enhanced CTLA-4 expression, long-term engraftment is unaffected. To address the temporal relationship between increased CTLA-4 exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 54 publications
2
19
0
Order By: Relevance
“…To address this, mice treated with CsA and anti-CD45RB also received daily recombinant IL-2 (rIL-2) at a dose that augments Treg number and HP in the absence of CsA (data not gen. In agreement, transplant studies suggest that anti-CD45RB promotes antigen-specific Tregs (25,29,54). For example, anti-CD45RB generates donor-specific tolerance that is abrogated with depletion of Tregs by anti-CD25.…”
Section: Cd45 Ligation Increases Nfat Activation In Tregssupporting
confidence: 52%
See 2 more Smart Citations
“…To address this, mice treated with CsA and anti-CD45RB also received daily recombinant IL-2 (rIL-2) at a dose that augments Treg number and HP in the absence of CsA (data not gen. In agreement, transplant studies suggest that anti-CD45RB promotes antigen-specific Tregs (25,29,54). For example, anti-CD45RB generates donor-specific tolerance that is abrogated with depletion of Tregs by anti-CD25.…”
Section: Cd45 Ligation Increases Nfat Activation In Tregssupporting
confidence: 52%
“…To rule out an effect on thymic output, we showed that anti-CD45RB increased Treg numbers in euthymic and thymectomized mice equally (Figure 2A). Concordantly, thymectomy did not prevent anti-CD45RB-induced prolongation of islet allograft survival by anti-CD45RB (29). This suggests that anti-CD45RB acts on Tregs in the periphery.…”
Section: Cd45 Ligation Expands Tregs By Promoting Interactions With Dcsmentioning
confidence: 60%
See 1 more Smart Citation
“…Recent studies correlated the effect of anti-CD45RB with up-regulation of CTLA-4 on T cells (6,7). Because CTLA-4 can deliver negative signals in T cell activation and may be expressed by regulatory T cells (Tregs), 6 anti-CD45RB-induced up-regulation of CTLA-4 may play an important role in deactivation of graft-reactive lymphocytes (8,9). In addition, induction of T cell anergy and formation of Th2 or Treg cells have been suggested in previous studies (4,10).…”
mentioning
confidence: 99%
“…In addition, we have previously shown that aCD45 treatment increases CD25 expression on most of the CTLA4-positive T cells. These CD25-positive cells from aCD45-treated mice exhibit Treg activity, suggesting that aCD45 induces Tregs (44). Approximately 70% of CTLA4-positive cells from naive mice treated with aCD45 also coexpressed Foxp3, suggesting that aCD45 may induce Tregs in vivo (D. Rothstein, unpublished data).…”
Section: Discussionmentioning
confidence: 99%